Desenvolvimento de índice de biodegradação de hidrocarbonetos de petróleo e derivados em água do mar usando Sistema de Inferência Fuzzy. - Vasconcelos, Gilson Gonçalves de (2015)
A fuzzy index for state/quality assessment (very low, low, medium, high and very high) of petroleum hydrocarbon biodegradation and derivatives in seawater is first proposed. The index combines information of a biological indicator - the yield of biomass growth, a chemical indicator - the variation hydrogenionic potential (pH) and a physical indicator - the variation of the surface tension and provides quantitative and qualitative classification of hydrocarbon biodegradation of petroleum and derivatives in seawater, which can be used for monitoring, optimization and process control. To evaluate the performance of the index, a case study of a process of diesel oil biodegradation by Candida lipolytica UCP 0988 in seawater was conducted, using data of twelve assays of a full factorial design 23, having as independent variables the initial pH, the initial biomass concentration and the initial concentration of diesel oil as responses variables the variation of pH, the variation of the biomass and the variation of the surface tension. From assays analyzed with the biodegradation index about 50% was rated as having medium quality, 8.3% low, 8.3% low / medium and 33.3% very low. The results were consistent with those expected by experts and validated the use of the index as a simple, effective and economical tool for quality assessing of petroleum hydrocarbon biodegradation and derivatives in seawater. The index developed has potential for application in the oil biodegradation processes and derivatives in rivers, lakes and soils.